All things bright and beautiful ebook - Herriot, James (All Creatures Great and Small, 2011)
From the #1 New York Times –bestselling author of All Creatures Great and Small : more true stories of a veterinarian in small-town Yorkshire, England.   After his first day on the job, James Herriot’s mentor warns him that the life of a country veterinarian is full of small triumphs and big disasters, but that he’d never be bored. From night visits to drafty barns during freezing northern England winters, to the beautiful vitality of rural life in the summertime, to the colorful menagerie of animals—and their owners—that pass through his office, Herriot experiences new challenges and joys every day. In these pages, Herriot trains under his eccentric boss Siegfried Farnon in a rustic English village, courts the woman that becomes his wife, and meets the people he would come to write about for a lifetime.